Neonatal resuscitation monitoring: A low-cost video recording setup for quality improvement in the delivery room at the resuscitation table - Olson, Linus; Bui, Xuan Anh; Mpamize, Allan; Vu, Hien; Nankunda, Jolly; Truong, Tung Thanh; Byamugisha, Josaphat; Dempsey, Tina; Lubulwa, Clare; Winroth, Axel; Helldén, Daniel; , NeoSupra & NeoSpirit Teams; et al. (Frontiers in Pediatrics, 2022)
Background: The quality of neonatal resuscitation after delivery needs to be improved to reach the Sustainable Development Goals 3.2 (reducing neonatal deaths to < 12/1000 live newborns) by the year 2030. Studies have emphasized the importance of correctly performing the basic steps of resuscitation including stimulation, heart rate assessment, ventilation, and thermal control. Recordings with video cameras have previously been shown to be one way to identify performance practices during neonatal resuscitation. Methods: A description of a low-cost delivery room set up for video recording of neonatal resuscitation. The technical setup includes rechargeable high-definition cameras with two-way audio, NeoBeat heart rate monitors, and the NeoTapAS data collection tools for iPad with direct data export of data for statistical analysis. The set-up was field tested at Mulago National Referral Hospital, Kampala, Uganda, and PhuSan Hanoi Hospital, Hanoi, Vietnam. Results: The setup provided highly detailed resuscitation video footage including data on procedures and team performance, heart rate monitoring, and clinical assessment of the neonate. The data were analyzed with the free-of-charge NeoTapAS for iPad and R statistical software, which allowed fast and accurate registration of all resuscitative events. All events were automatically registered and exported to statistical software for further analysis. Conclusions: Video analysis of neonatal resuscitation is an emerging quality assurance tool with the potential to improve neonatal resuscitation outcomes. Our methodology and technical setup are well adapted for low and lower-middle-income settings where improving neonatal resuscitation outcomes is crucial. This delivery room video recording setup also included two-way audio communication that potentially could be implemented in day-to-day practice or used with remote teleconsultants.